Sabah Fresh Chili / Norny Yusnita Jening ... [et al.] - Jening, Norny Yusnita; Muntek, Wan Juraidah; Amir Ali, Faranimah; Simin, Rohani; Abdul, Rosni (2010)
Sabah Fresh Chili is one of Enterprises in Malaysia that run a business of producing various chilies. It is located in a strategic area which is at Kampung Timbang Dayang in Kota Belud. There are few factors that affect SFC to choose the location and it will be explain later in introduction. In addition, there are twenty one workers in SFC who will co-operate together to ensure the business run efficiently. SFC administrative part play an important role to lead all workers carries out different task accordingly. Apart from that, SFC will be the manufacturer, retailer, wholesaler and E-intermediaries for customer in order to ensure the business can serve more customers at the same time to maintain profitability. How SFC attracts more customers instead of being manufacturer and so on will be includes in marketing plan. Other than thal. there are several steps on how to produce chili and what are the steps is mentioned in operation part. Nevertheless, SFC will try to avoid from any wastage depends of the financial statement as the most importance part for profitability of business. SFC is trying to face with any challenges comprises of different competitors, economy problem and so on in order to be better in the future. Besides that, it can also be the guidelines for SFC to correct any possible mistake as a new business maker may face. Thus, help the business to growth well and achieve the goals to be the BEST CHILIES SUPPLIER through out ASIAN .